Aluminium rolling : processes, principles & applications - Singh, R. V. (McGraw-Hill's AccessEngineering., 2011)
A. Dedication -- B. The reflections -- C. Preface -- D. Acknowledgements -- E. Author's profile -- F. Section - i -- 1. Specifications of aluminium alloys -- Introduction -- Special properties of aluminium -- Applications -- Standards for alloys of aluminium -- World standards -- More about alloys -- Tempers -- Heat treatment processes -- Surface treatment - a brief review -- Reference tables -- Bibliography and references -- 2. Melting and holding furnaces, furnace controls and molten metal treatments -- Introduction -- Aluminium melting and holding furnaces -- Melting loss -- Casting -- Melt impurities, degassers and inclusions (gaseous and solid) -- Degassing -- Chlorination -- Molten metal filtration -- Molten metal level control -- Grain refining: introduction -- Molten aluminium stirring -- Bibliography and references -- 3. D.c. Casting, electromagnetic casting, continuous strip casting, scalping, soaking and preheating -- Introduction -- Conventional d.c. Casting -- Introduction to electromagnetic d.c. Casting -- A comparative analysis of the modern casting technologies -- Continuous strip casting (equipment and technology) -- Hazelett belt caster -- Caterpillar casting machine/block caster -- Roll casters -- Single roll: continuous drag casting -- Scalping -- Preheating, homogenising and soaking -- Bibliography and references -- 4. Introduction to hot rolling, cold rolling, foil rolling and basic philosophy of product quality control -- Introduction -- Types of rolling -- Hot rolling of aluminium -- Aluminium cold rolling and foil rolling -- Conventional terms used in rolling -- Hot rolling of aluminium and hot rolling mills -- Special features of modern hot-mills -- The latest advances in hot rolling technology -- Hot mill roll coolant -- Hot mill coolant filtration -- Hot-mill roll brushing -- Introduction to cold rolling -- Shape control philosophy -- Roll bend control -- Backup roll chatter - resonance - 'fifth octave chatter' -- Mill drive characteristics -- Bibliography and references -- 5. Theories of rolling -- Introduction -- Bite -- Neutral point, neutral plane, no-slip angle -- Forward slip -- Observations and conclusions -- Flow of material and the criteria of yielding -- External friction -- Brown's investigation -- Plastic deformation: theories of rolling -- Rolling load and mean specific roll pressure -- Bibliography and references -- 6. Quality control automations -- Introduction -- Factors affecting the strip thickness -- Analysis -- General arrangement in a mill -- Mill stiffness -- Material stiffness -- Gauge, profile and shape -- Elastic/plastic curves -- Load control mode -- Position control mode -- Summary -- Effectiveness of gauge control -- Entry tension and its control -- Types of error feed and controls Gauge error feedback control -- Gauge-meter control -- Mass-flow control -- Thickness measuring gauges -- Types of product optimization -- Anatomy of a proposed optimization system -- Bibliography and references -- 7. Cold rolling coolant base, coolant additives and tribology in rolling -- Introduction -- Chemical considerations -- Base oil -- Reduction additives -- General considerations -- Hydrodynamic film forming characteristics -- Tests to assess relative merits of lubricants -- Comments on the various tests on load bearing and deformation in context to rolling -- Comments -- Conclusion regarding coolant and additive -- Tribology in rolling -- Bibliography and references -- 8. Rolls and roll shells, roll grinding, grinding wheels and roll inspection -- Introduction -- Forged rolls and cast rolls -- Grinding and maintenance of rolls -- Definitions -- Recommended grinding practices -- Bibliography and references -- 9. Annealing and heat-treatments, levelling and various finishing operations, quality control systems and handling -- Annealing: furnaces and processes (refer chapter 1 also) -- Stage of intermediate annealing -- Finishing -- Tension levelling -- Slitting line -- Strand separator -- Cut-to-length line -- Other finishing operations -- Electroplating -- Painting and other organic coating -- Surface inspection and on line statistical process-control system -- Material handling systems -- Bibliography and references -- G. Section - ii -- 10. Supportive/complementary technical extensions -- Conventional terms used in rolling and connected processes -- Finishing and general -- More information on hazelett and caterpillar casting (block caster or caster ii) -- Thickness measuring gauges -- Common properties of aluminium -- Water corrosion on aluminium -- From the information desk -- Problems, causes and cures -- Bibliography and references -- H. Section - iii -- 11. History of aluminium, introduction to production processes and elementary metallurgy -- History of aluminium -- Introduction to aluminium: a metal with special properties -- Growth potential of aluminium and statistical information -- Production processes -- Special points -- Alternative process for al_2o_3 -- Alumina to primary aluminium (hall-heroult process) -- Introduction to the metallurgical structure of aluminium -- Factors influencing the grain size and homogeneity of the casting -- Fabrication-process flow sheet -- Grain growth in d.c. Casting -- Environmental issues -- Aluminium and health -- Bibliography and references